Optimization of UHPFRC beams subjected to bending using genetic algorithms - Ćirović, Goran; Radonjanin, Vlastimir; Trivunić, Milan; Trivunić, Milan; Nikolić, Dragan (Journal of Civil Engineering and Management, 2014)
Ultra high performance fibre reinforced concrete (UHPFRC) is cementitious composite with very high strength, and when compared with ordinary concrete it is a more superior material both in terms of its mechanical properties and its durability. In order to predict the behaviour of UHPFRC beams, first of all, experiments were carried out to investigate the mechanical properties of composites containing 2% and 4% of steel fibres. Following this, four beams of 2 m in length were tested by subjecting to four point bending. Two beams contained only micro steel fibres, while the remaining two contained conventional steel bar reinforcement. On the basis of experimental studies and recommendations by the AFGC for UHPC, the behaviour of the beams was modelled and optimization was carried out using genetic algorithms (GA) according to the criterion of minimum price. In this paper, the prices of individual UHPFRC beams are also shown in comparison with beams, which contain steel bars or prestressed reinforcement.